JERUSALEM'S SIGNIFICANCE To WORLD JEWRY: The Covenant and the Promised Land - Jospe, Raphael (Journal of Dharma, 1993)
The biblical account of God's covenant with Abraham and his descendants begins with a territorial imperative. The promised land is thus not incidental to Israel's covenant with God, but lies, as an essential component, at its very foundation. Within the promised land, the borders of which were never constant and fluctuated historically, the city of Jerusalem occupies